Reintroducing materials for sustainable design : design process and educational practice - Bak-Andersen, Mette (Routledge, 2021)
"Reintroducing Materials for Sustainable Design provides instrumental theory and practical guidance to bring materials back into a central role in the design process and education. To create designs that are sustainable and respond to current environmental, economic, and cultural concerns, practitioners and educators require a clear framework for materials use in design and product manufacturing. While much has been written about sustainable design over the last two decades, outlining systems of sustainability and product criteria, to design for material circularity requires a detailed understanding of the physical matter that constitutes products. Designers must not just know of materials but know how to manipulate them and work with them creatively. This book responds to the gap by offering a way to acquire the material knowledge necessary to design physical objects for sustainability. It reinforces the key role and responsibility of designers and encourages designers to take back control over the ideation and manufacturing process. Finally, it addresses the educational practice involved and the potential implications for design education following implementation, looking at didactics, facilities and expertise. This guide is a must-read for designers, educators and researchers engaged in sustainable product design and materials"- Resumé vydavatel
Keywords: udržitelný rozvoj; udržitelná architektura; ekodesign; sustainable development; sustainable architecture; ecodesign; produktový design; elektronické knihy; příručky; electronic books; handbooks and manuals